2011
DOI: 10.1007/s11090-011-9330-3
|View full text |Cite
|
Sign up to set email alerts
|

Low Pressure Radio Frequency Ammonia Plasma Surface Modification on Poly(ethylene terephthalate) Films and Fibers: Effect of the Polymer Forming Process

Abstract: We investigated the effect of a polyethylene terephthalate (PET) forming process on radiofrequency ammonia plasma surface-treated PET flat films and fibres obtained by melt blowing. Ammonia plasma treatment allowed for the incorporation of amino functionalities on both the film and fibre surfaces, with higher values observed at very short treatment times. This plasma treatment also induced polymer chain scissions which were observed as the formation of hydrophilic nodules that coalesced together and were loose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
3
11
0
Order By: Relevance
“…After plasma treatment, the C/O ratio increased to 2.4, meaning that oxygen containing chemical groups were reduced during the plasma treatment, due to PLCL surface degradation. This observation can be explained by ester group scissions followed by decarboxylation step as already described in literature on polyesters 26 - 28 . This hypothesis was also correlated by the significant drop in the relative area of O–C = O peak in the C1s HR spectrum (Fig.…”
Section: Resultssupporting
confidence: 78%
“…After plasma treatment, the C/O ratio increased to 2.4, meaning that oxygen containing chemical groups were reduced during the plasma treatment, due to PLCL surface degradation. This observation can be explained by ester group scissions followed by decarboxylation step as already described in literature on polyesters 26 - 28 . This hypothesis was also correlated by the significant drop in the relative area of O–C = O peak in the C1s HR spectrum (Fig.…”
Section: Resultssupporting
confidence: 78%
“…With the development of polymer industry and NTP technology, more and more gases were used as discharging gas for polymer web surface treatments. For example, for the aim of improving hydrophilicity, the discharge gas can be the non-polymerisable gas such as Ar [96,97], He [98,99], Air [100][101][102], O 2 [103,104], N 2 [104,105], NH 3 [106], CO 2 [107,108], while CF 4 [109][110][111] or other CF-based compounds monomers [112,113] were used to obtain hydrophobic film. Reactive O 2 plasma is known to introduce a mixture of mainly carboxyl group (-COOH) and hydroxyl group (-OH) functionalities, while N 2 or NH 3 plasma introduces amines on the polymeric surfaces.…”
Section: Plasma Surface Treatmentmentioning
confidence: 99%
“…For this purpose, plasma treatments were used in many studies that have been carried out on the modification of PET . Inagaki et al investigated the modification of PET by Ar, O 2 , H 2 , N 2 , and NH 3 plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, plasma treatments were used in many studies that have been carried out on the modification of PET. [4][5][6][7][8] Inagaki et al investigated the modification of PET by Ar, O 2 , H 2 , N 2 , and NH 3 plasmas. They found that the O 2 , Ar, and N 2 plasmas preferably modified the CH 2 groups or phenyl rings while H 2 and NH 3 plasma mainly modified ester groups.…”
mentioning
confidence: 99%